Consequentializing Moral Dilemmas - Suikkanen, Jussi (Journal of moral philosophy, 2020)
The aim of the consequentializing project is to show that, for every plausible ethical theory, there is a version of consequentialism that is extensionally equivalent to it. One challenge this project faces is that there are common-sense ethical theories that posit moral dilemmas. There has been some speculation about how the consequentializers should react to these theories, but so far there has not been a systematic treatment of the topic. In this article, I show that there are at least five ways in which we can construct versions of consequentialism that are extensionally equivalent to the ethical theories that contain moral dilemmas. I argue that all these consequentializing strategies face a dilemma: either they must posit moral dilemmas in unintuitive cases or they must rely on unsupported assumptions about value, permissions, requirements, or options. I also consider this result’s consequences for the consequentializing project.